(untitled) (Asian Education Studies, 2017)
E-learning has become a necessity for all elements of the communication process in today’s world. Education, in all its many shapes and forms from dialogue to dialogic, is dependent upon that communication process. Manifestations of technology, including networks, devices and applications, contributed to the global spread of e-learning. The concept and application of continuing education at any time and place has emerged with individual differentiation and efficient performance gaining more momentum. The global labour market and modern technology has had a mutual effect as it has become necessary for people to acquire e-learning competencies to access the labor market with the required performance levels. Therefore, the related research problem addressed by this paper is articulated in this question: "To what extent do the students at Princess Nourah bint Abdulrahman University possess e-learning competencies to qualify them for the labour market?” This research reached results indicating, for instance, that the subjects’ possession of competencies in dealing with the computer was medium. However, the subjects’ possession of the skills necessary to deal with the Internet was high. Further, the subjects’ possession of e-learning culture was medium. The researcher recommended using a standardised set of e-learning skills in the development of IT educational courses and developing an educational training program for the students to enhance their competencies. It is also recommended that the students’ pre-University programs need evaluation to determine the extent to which they cover the content that leads to these competencies.